How Important Are Mental and Physical Health in Career and Family Choices? - Guido Cozzi; Noemi Mantovan; Robert M. Sauer (Institute of Labor Economics (IZA), 2024)
We present a dynamic life-cycle model of women's labor supply, marriage, and fertility choices that explicitly incorporates mental and physical health. Correlated mental and physical health production functions are simultaneously estimated, including the endogenous decisions to seek psychotherapy and smoke cigarettes as health accumulation factors. The model is estimated by the Simulated Method of Moments with Indirect Inference using data from the British Household Panel Study. Results indicate that mental health has a stronger impact on labor supply than physical health. At the same time, estimates show that working part-time and full-time aect both mental and physical health. Moreover, we nd dierences in the interaction of the two forms of health on other life dynamics, with better mental health having stronger impacts on marriage and fertility outcomes than physical health. Counterfactual simulations reveal that not only permanent, but also temporary shocks to health and employment have long-lasting eects on life decisions, life satisfaction, and income due to their interaction with fertility. Finally, policy experiments show that lower costs for psychotherapy and increased costs of cigarettes would substantially increase fertility but decrease employment, while a decrease in childcare costs for employed women would increase both fertility and labor supply, supporting women's overall health.
Keywords: I12; J12; J13; J16; J22; 330; female labor supply; marriage; fertility; career; family; mental health; physical health; psychotherapy; smoking; discrete choice dynamic programming models; structural estimation; simulated method of moments; indirect inference